Tensile Properties Prediction of Polypropylene Reinforced Woven Kenaf Composite using Micromechanical Models - Khairul Anuar, Daniel Affendy Amri (IRC, 2020)
Natural fibre reinforced composites are increasingly used in various commercial applications but there has been little theoretical modelling done related to polypropylene (PP) reinforced woven kenaf composite. The objectives of this project were to predict the tensile properties of PP-Kenaf composite by applying Rule of Mixture (ROM) equations and to validate the results of tensile properties with existing experimental data from previous study. The reinforcing fibre was woven before undergoing compression molding process with the matrix. PP was used as the matrix and kenaf fibre as reinforcement. The composition used was 70:30 wt.% (PP-Kenaf). Since the kenaf fibre was woven, 15 wt.% would be in longitudinal direction and another 15 wt.% in transverse direction.